A gravity analysis of inter-provincial trade - Beverly J. Lapham; Daniel Teeter (Queen's University, Department of Economics, 2023)
In this paper, we provide evidence of frictions associated with trade in goods and services among Canadian provinces. We examine empirical relationships between sector- and industry-level trade flows and trading frictions associated with intra-provincial trade, inter-provincial trade, and international trade. We also develop a novel method for estimating the magnitude of differences across provinces, industries, and time in relative inter-provincial trade frictions. We find that the ranking of these relative inter- provincial frictions across provinces and the degree of regional dispersion varies considerably across the sectors and industries we study. In addition, we find considerably more geographic dispersion in the frictions that provinces face as sellers of goods and services than those which they face in their roles as buyers. Finally, we evaluate quantitative associations between two Canadian inter-provincial regional trade agreements and inter-provincial trade flows for a variety of industries. We document considerable variation across sectors and manufacturing sub-industries in our estimates of the relationships between these provincial trade agreements and trade flows. For example, trade agreements signed among western provinces around 2010 are positively associated with trade flows in the mining sector, textiles, petroleum, and transportation equipment, but are negatively associated with trade flows in agricultural goods and manufactured food products.
Keywords: F13; F14; F15; 330; Intra-regional and inter-regional trade frictions; Trade agreements; Structural Gravity; Canada